MINAT MEMBELI MASYARAKAT SUB URBAN TERHADAP PRODUK RITEL - Pandu Adi Cakranegara (Universitas La Tansa Mashiro, 2021)
A suburban community is a unique community. Suburban communities are generally newcomers who come to the city to work and live in suburban areas because the affordable housing prices are comparable to those in the city center. Suburban communities have the characteristics of having a modern mindset and high purchasing power compared to indigenous peoples who live in suburban areas. This study uses a mixed method using observation, interviews, and questionnaires. This study shows that location is a significant factor in suburban communities in buying a product. Urban communities also pay attention to the brand and perception of a product. These things reflect how the values of a busy sub-urban society tend to want to be practical. High purchasing power enables suburban communities to consume better quality goods and services. In the future, it is necessary to study further how other factors can influence the variables in this study, such as technology variables that enable online shopping.